INDONESIA’S PALM OIL EXPORT TO MALAYSIA AND THAILAND - Jati, Kumara (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
The economic recovery after the COVID-19 pandemic has significantly increased the demand for palm oil in Indonesia and globally. This study analyzes the regulation and valuation of palm oil trade between Indonesia and Malaysia and Thailand. In addition, the study focuses on Indonesia's exports to her two major countries in Southeast Asia. Based on prescriptive legal analysis, relevant stakeholders have enacted several new regulations to ensure the stability and availability of palm cooking oil. The Indonesian central government has enacted several new regulations related to palm cooking oil to ensure availability and affordability in the domestic market as well as to support exports abroad. A Structural Time Series Model (STSM) estimates that the trade value of Indonesian palm oil exports to Malaysia and Thailand will stabilize in 2022. Indonesia's export policy needs to take into account cyclical, seasonal and irregular patterns. Stakeholders should check for irregular factors such as 2020, 2021, the economic crisis, and the COVID-19 pandemic. Competent authorities must consider all aspects, especially international prices and palm oil exports, in order to implement best guidelines in a timely manner and to further review existing regulations. All palm oil stakeholders have adapted to the new regulations introduced by the government to ensure domestic supplies of palm cooking oil are available and affordable, and the remaining palm oil and its derivatives can be exported abroad.